Study cases of thermal conductivity prediction from P-wave velocity and porosity - Esteban, L.; Pimienta, L.; Sarout, J.; Delle Piane, C.; Haffen, S.; Geraud, Y.; Timms, Nicholas Eric (Pergamon, 2015)
Laboratory measurements of porosity, P-wave velocity and thermal conductivity from samples from two geothermal reservoirs in France and Australia are compared to the predictions from different models involving mineralogical considerations, and effective medium theory models yields <10% error in dry and saturated conditions in the Australian aquifer, and <30% deviation under saturated conditions in the French reservoir. Thermal conductivity derived from models involving detailed mineralogy is in good agreement with laboratory-measured data. Possible explanations for minor discrepancies using SEM/XRD include the effects of secondary minerals (i.e. ±undetected carbonates and fine particles) and the hydration of clays.